Study of Green Energy Production in INTI’s 3 kJ Plasma Focus Device - Arwinder, Singh; Pavandeep, Kaur; Jeya Gopi, Raman; Teh, Thiam Oun; Saw, Sor Heoh; Lee, Sing (INTI International University, 2022)
Green and sustainable energy production has recently become a topic of great interest due to limited natural resources such as oil and gas, the increasing political turmoil and environmental concerns over temperature increase due to greenhouse effect. In INTI, a basic study of the creation of green energy or plasma energy was carried out. Plasma can be understood as the highest energy state of matter. When matter is heated to a high enough temperature, it is ionized into positive and negative charged particles with potential of energy production. To study such energy production, INTI’s 3 kJ Mather- type plasma focus machine is charged to 13.5 kV and discharged into 3 Torr deuterium gas. This machine produces a current sheet that travels at extremely high speeds which will heat and compress (pinch) the plasma above the anode to produce extremely high temperature. This pinch undergoes instabilities and breaks up releasing intense electromagnetic radiation (including fusion energy). To make fusion energy more reliable and commercially viable, continuous fusion reaction is needed and plasma should be sustained over a long period of time. The leading candidate for a fusion reactor is a different plasma machine call a tokamak, but the plasma focus is emerging as a more compact contender.